Funkcja stylistyczna wypowiedzi w perspektywie lingwistyki porównawczej - Kiklewicz, Aleksander (Stylistyka, 2020)
The tendency in researching language stylistics is that researchers rather start from a certain style and assign language properties to it, including syntactic ones. In the presented article, which is based on the model of functional syntax (Kiklewicz 1999; 2004), the author suggests an opposite research perspective, that is analysis of stylistic properties of specific kinds of syntactic structures. Being completion of the former description rule this research suggestion contributes to a comprehensive presentation of language competence where stylistic markedness of language units constitutes an important aspect. For this reason and due to isolation of categorical content of the function, scope of its meaning and reference the suggestion depicted is so helpful in comparing languages.